Better humans? : understanding the enhancement project - Hauskeller, Michael; Cambridge eBooks (Durham : Acumen Publishing, 2013)
Developments in medical science have afforded us the opportunity to improve and enhance the human species in ways unthinkable to previous generations. Whether it's making changes to mitochondrial DNA in a human egg, being prescribed Prozac, or having a facelift, our desire to live longer, feel better and look good has presented philosophers, medical practitioners and policy-makers with considerable ethical challenges. But what exactly constitutes human improvement? What do we mean when we talk of making 'better' humans? In this book Michael Hauskeller explores these questions and the ideas of human good that underpin them. Posing some challenging questions about the nature of human enhancement, he interrogates the logic behind its processes and examines the justifications behind its criteria. Questioning common assumptions about what constitutes human improvement, Hauskeller asks whether the criteria proposed by its advocates are convincing. The book draws on recent research as well as popular representations of human enhancement from advertising to the internet, and provides a non-technical and accessible survey of the issues for readers and students interested in the ethics and politics of human enhancement.
Introduction -- Becoming smarter -- Making better humans better -- Feeling better -- Becoming truly human -- Living longer -- Going cyber -- Looking good -- Getting stronger -- Being at home in the world -- Concluding remarks.
Title from publisher's bibliographic system (viewed on 02 Oct 2015).
Keywords: Bioethics; Biotechnology -- Moral and ethical aspects; Philosophy; Electronic books